2015
DOI: 10.18632/oncotarget.3360
|View full text |Cite
|
Sign up to set email alerts
|

ROCK inhibition promotes microtentacles that enhance reattachment of breast cancer cells

Abstract: The presence of circulating tumor cells (CTCs) in blood predicts poor patient outcome and CTC frequency is correlated with higher risk of metastasis. Recently discovered, novel microtubule-based structures, microtentacles, can enhance reattachment of CTCs to the vasculature. Microtentacles are highly dynamic membrane protrusions formed in detached cells and occur when physical forces generated by the outwardly expanding microtubules overcome the contractile force of the actin cortex. Rho-associated kinase (ROC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 56 publications
1
16
1
Order By: Relevance
“…Additionally, priming with Fasudil may decrease cell survival in the bloodstream via impaired tolerance to shear stress (97). Whereas previous studies have reported conflicting findings on the effects of ROCK inhibition on cell invasion (98-100), short-term treatment with Fasudil did not show adverse effects, unlike chronic ROCK targeting. We also reveal that Fasudil priming impairs the ability of metastasized cells to create a fibrotic refuge, potentially enhancing their vulnerability to subsequent chemotherapy (67).…”
Section: Discussioncontrasting
confidence: 67%
“…Additionally, priming with Fasudil may decrease cell survival in the bloodstream via impaired tolerance to shear stress (97). Whereas previous studies have reported conflicting findings on the effects of ROCK inhibition on cell invasion (98-100), short-term treatment with Fasudil did not show adverse effects, unlike chronic ROCK targeting. We also reveal that Fasudil priming impairs the ability of metastasized cells to create a fibrotic refuge, potentially enhancing their vulnerability to subsequent chemotherapy (67).…”
Section: Discussioncontrasting
confidence: 67%
“…42 Recent studies have shown that ROCK inhibition can promote the reattachment of breast cancer cells in circulation, which correlates with our conclusions. 43 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies described the inhibitory effects of ROCK blockers on in vitro adherent tumor cell migration and invasion (Gutjahr et al, 2005;Torka et al, 2006;Patel et al, 2014), although recent data showed that ROCK inhibition increases the metastatic potential of nonadherent breast tumor cells by increasing their reattachment efficacy (Bhandary et al, 2015). ROCKs have been implicated in the pathogenesis of cancer and several aspects of human tumor progression (Rath and Olson, 2012).…”
Section: Cancermentioning
confidence: 99%